Simultaneous Determination of Pyrethrins, Pyrethroids, and Piperonyl Butoxide in Animal Feeds by Liquid Chromatography-Tandem Mass Spectrometry - Xin Xu; Lisa A. Murphy (Toxins, 2023)
The presence of insecticides like pyrethrins and synthetic pyrethroids, combined with the synergist piperonyl butoxide, in animal feeds can pose a risk to both animal and human health by contaminating the food chain. In this study, a simple and fast method was developed for the simultaneous determination of these compounds in contaminated animal feeds using liquid chromatography–tandem mass spectrometry (LC-MS/MS). Sample preparation was carried out using a QuEChERS-based approach, and the method was validated with acceptable accuracy ranging from 84 to 115% and precision below 10%. The limit of detection (LOD) and limit of quantification (LOQ) were between 0.15 and 3 and 1 and 10 µg/kg, respectively. The method detected insecticide contaminations in various livestock and poultry feeds. Furthermore, the method was applied to a toxicology case, where it identified and quantified piperonyl butoxide and deltamethrin in the submitted horse feed sample. These results demonstrate that the method can be a valuable tool in animal health and food safety diagnostic applications, as well as veterinary toxicology investigations concerning pyrethrin-related feed contamination.